Implementasi Strategi Scaffolding Dalam Pembelajaran Pancasila Di Sekolah Dasar - Muhammad Hafiz Anshari; Ahmad Suriansyah; Arta Mulya Budi Harsono (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The scaffolding strategy represents a learning approach in which teachers act as guides and supporters to help students achieve their learning goals. The primary focus of this strategy is to provide appropriate and effective support so that students can learn more independently and achieve predetermined learning goals. The aim of this research is to illustrate how the scaffolding strategy is implemented in Pancasila education at SDN Sungai Miai 2 Banjarmasin, while also identifying the influences, supports, obstacles, and implications of its development. The research method used is a qualitative case study with data collection techniques consisting of semi-structured interviews and direct observation of the implementation of learning activities. The collected data were then analyzed using thematic analysis to identify patterns of meaning that emerge from field findings. Research findings demonstrate that the use of scaffolding strategies in Pancasila education at the primary school level effectively helps students better understand Pancasila values. Through this strategy, students demonstrate higher levels of activity and engagement in learning, as well as improved skills in analyzing and evaluating information.